(untitled) (Human Factors in Design, 2021)
Within the scope of industrial megaprojects, such as a large-scale maintenance campaign for an oil platform, planning for tasks that will be executed in highly dynamic environments – defined by variability, uncertainty, and unforeseen events – is a challenging job. The Ergonomic Work Analysis (EWA) by the maintenance planning technicians showed that, despite the different strategies in use, there are limits in the possibility of predicting a future context. Thus, planning is a collective process of reducing uncertainty, but it requires instrumentalization of the players involved therewith.